Intimate physical contact between people from different households during the COVID-19 pandemic: a mixed-methods study from a large, quasi-representative survey (Natsal-COVID). Issue 2 (9th February 2022) - Sonnenberg, Pam; Menezes, Dee; Freeman, Lily; Maxwell, Karen J; Reid, David; Clifton, Soazig; Tanton, Clare; Copas, Andrew; Riddell, Julie; Dema, Emily; Bosó Pérez, Raquel; Gibbs, Jo; et al.
Abstract : Objectives: Physical distancing as a non-pharmaceutical intervention aims to reduce interactions between people to prevent SARS-CoV-2 transmission. Intimate physical contact outside the household (IPCOH) may expand transmission networks by connecting households. We aimed to explore whether intimacy needs impacted adherence to physical distancing following lockdown in Britain in March 2020. Methods: The Natsal-COVID web-panel survey (July–August 2020) used quota-sampling and weighting to achieve a quasi-representative population sample. We estimate reporting of IPCOH with a romantic/sexual partner in the 4 weeks prior to interview, describe the type of contact, identify demographic and behavioural factors associated with IPCOH and present age-adjusted ORs (aORs). Qualitative interviews (n=18) were conducted to understand the context, reasons and decision making around IPCOH. Results: Of 6654 participants aged 18–59 years, 9.9% (95% CI 9.1% to 10.6%) reported IPCOH. IPCOH was highest in those aged 18–24 (17.7%), identifying as gay or lesbian (19.5%), and in steady non-cohabiting relationships (56.3%). IPCOH was associated with reporting risk behaviours (eg, condomless sex, higher alcohol consumption). IPCOH was less likely among those reporting bad/very bad health (aOR 0.54; 95% CI 0.32 to 0.93) but more likely among those with COVID-19 symptoms and/or diagnosis (aOR 1.34; 95% CI 1.10 to 1.65). Two-thirds (64.4%) of IPCOH was reported as being within a support bubble. Qualitative interviews found that people reporting IPCOH deliberated over, and made efforts to mitigate, the risks. Conclusions: Given 90% of people did not report IPCOH, this contact may not be a large additional contributor to SARS-CoV-2 transmission, although heterogeneity exists within the population. Public health messages need to recognise how single people and partners living apart balance sexual intimacy and relationship needs with adherence to control measures.